Factors influencing purchase intentions for glass products with Chinese cultural elements - Qingfeng, Liu; Wan Omar, Wan Noor Faaizah; Ahmad, Masitah (Faculty of Art and Design, 2025)
Glass products featuring Chinese cultural elements are mainly found in collections, exhibitions, and educational institutions. However, their sale as everyday necessities is less common. Research on these products, especially regarding perceived benefits and purchase intentions, remains limited. This study focuses on contemporary Chinese glass products with cultural elements, referencing literature on product innovation, emotional design, and the cultural creative industry, and explores how perceived benefits influence purchase intention. The study begins by classifying glass products based on their cultural aspects and selecting the samples for empirical analysis. Using online questionnaires, 503 valid responses were collected, and hypotheses were tested. The results show that the target group holds a positive attitude towards perceived benefits and also demonstrates a willingness to purchase such products. Hypothesis testing indicates that beauty value and identity benefits significantly influence purchase intention. Finally, the study offers feasible strategies for developing glass products with Chinese cultural elements.